Sosialisasi Pembuatan Mesin Pirolis Plastik Sederhana sebagai Alat Pengolah Sampah Plastik Menjadi Bahan Bakar Minyak di Desa Lopo Kabupaten Gorontalo - Muhammad Yunus; Nursia Madjid; Septiana Kurniasari; Irsan Irsan; Citron S. Payu; Hendra Hendra (Panrita Inovasi: Jurnal Pengabdian Kepada Masyarakat, 2022)
Garbage is something that humans throw away because it can no longer be used. An environment with a buildup of garbage can cause various problems such as hygiene, health, beauty, environmental pollution, and social issues. One of the problems regarding waste is located in Lopo Village-Gorontalo District. Garbage is thrown away and then burned, especially plastic waste. The combustion results can undoubtedly pollute the environment. This happens due to the need for more guidance and community empowerment in recycling waste into something that can be useful. One of the solutions for handling waste into something that can be useful is to convert plastic waste into fuel oil through the socialization of making a simple plastic pyrolysis machine. This socialization activity provides an understanding of waste and its impact on the environment, methods of waste management, and how to make a simple plastic pyrolysis machine. The participants were very enthusiastic about participating in this socialization because they learned how to process plastic waste into fuel and make simple plastic pyrolysis machines that can be products of high economic value